Concerns of Hydrothermal Degradation in CAD/CAM Zirconia - Kim, J.-W. (SAGE Publications, 2010)
Zirconia-based restorations are widely used in prosthetic dentistry; however, their susceptibility to hydrothermal degradation remains elusive. We hypothesized that CAD/CAM machining and subsequent surface treatments, i.e., grinding and/or grit-blasting, have marked effects on the hydrothermal degradation behavior of Y-TZP. CAD/CAM-machined Y-TZP plates (0.5 mm thick), both with and without subsequent grinding with various grit sizes or grit-blasting with airborne alumina particles, were subjected to accelerated aging tests in a steam autoclave. Results showed that the CAD/CAM-machined surfaces initially exhibited superior hydrothermal degradation resistance, but deteriorated at a faster rate upon prolonged autoclave treatment compared with ground and grit-blasted surfaces. The accelerated hydrothermal degradation of CAD/CAM surfaces is attributed to the CAD/CAM machining damage and the absence of surface compressive stresses in the fully sintered material. Clinical relevance for surface treatments of zirconia frameworks in terms of hydrothermal and structural stabilities is addressed.